The correlation between neuropathic pain incidence and vitamin D levels in patients with chronic low back pain (Annals of Medical Research, 2021)
Aim: The present study aimed to investigate the correlation between neuropathic pain incidence and vitamin D levels in chronic mechanical low back pain.Material and Methods: Sixty patients (36 females, 24 males) with chronic mechanical low back pain (CMLBP) were included in the study. Leeds Assessment Neuropathic Symptoms and Signs Scale (LANSS), Beck Depression Inventory (BDI), and Visual Analogue Scale (VAS) were applied to the patients. Patient vitamin D levels were measured.Results: It was determined that the neuropathic low back pain incidence was 0.20. No statistically significant difference was determined between the neuropathic pain incidence in the group with subnormal vitamin D values and the group with normal vitamin D values (p = 0.292). The incidence of neuropathic pain was higher in the group with subnormal vitamin D levels when compared to the group with normal vitamin D values. Conclusion: It was demonstrated that neuropathic low back pain was more frequent among CMLBP patients with subnormal vitamin D values when compared to patients with normal vitamin D levels, albeit not statistically significantly. Vitamin D deficiency should be reviewed in the evaluation of CMLBP, neuropathic component of which was not well defined, and its treatment and management requires a multidisciplinary approach, and vitamin D treatment should be considered when necessary.
Keywords: Low back pain; neuropathic pain; Vitamin D